The effects of joints on the moisture behaviour of rain exposed wood: a numerical study with experimental validation. Issue 1 (2nd January 2021) - Niklewski, J.; Fredriksson, M.
ABSTRACT: Joints in timber structures are particularly vulnerable to degradation due to their tendency to trap moisture. The mechanisms involved, and their effect on the moisture conditions of wood, are here investigated numerically. The horizontal member of a rail and post-type configuration is modelled numerically by a two-dimensional diffusion model with material properties for Norway spruce. Contact areas are assumed to be fully wetted when the specimen is exposed to free water but are unable to interact with the ambient air. Water that is absorbed through such areas cannot dry out through the same surface and is instead redistributed. The model was validated against experimental data, both previously unpublished data and data obtained from the literature, including both laboratory and outdoor exposure. The numerical solutions were, in general, consistent with the measured data. The model provides a simple, yet accurate, method to estimate the moisture conditions in certain types of wood joints. In addition, the spatial distribution of time spent above 25% moisture content was calculated, in order to investigate the suitability of the model for durability applications.